PENGARUH KONSELING DIET RENDAH PURIN DAN TINGGI OMEGA-3 TERHADAP KADAR ASAM URAT PASIEN GOUT RAWAT JALAN DI RUMAH SAKIT dr. A.K. GANI PALEMBANG TAHUN 2015 - Muzakar Muzakar; Terati Terati; Mulizha Mulizha (Publikasi Penelitian Terapan dan Kebijakan, 2018)
Hyperuricemia is an increased concentration of uric acid in the blood as a trigger gout. Consumption of a balanced diet, limiting consumption of purine and choose food sources of omega-3 which helps reduce the pain of gout is an ef ort right diet for patients. In order to accelerate the healing process, to change the behavior of the patient to be able to cope with gout can be done by using the media leaflet nutritional counseling. The purpose of this study was to determine the ef ect of counseling low-purine diet and high in omega-3 against uric acid levels in gout patients dr. AK Gani Palembang.This type of research is a quasi-experimental research. In the entire study population of gout patients who seek treatment at the hospital dr. AK Gani Palembang. Samples numbered 40 people, divided into two groups: the treatment and comparison drawn by purposive sampling sampling techniques eksidental. Analysis and data processing is computerized statistical paired t test.Results of univariate analysis showed the characteristics of respondents as many as 76% of respondents were female and the majority of respondents aged 46-55 years (35%). On the results of the analysis of the intake of macro and micro nutrients in the comparison group showed only on energy intake largely classified as good (55%), while the energy treatment group (60%), fat (65%), omega-3 (55%), and purine (80%) has been quite good.Results of bivariate analysis showed an average reduction in uric acid levels before and after a low-purine diet counseling in the amount of 2.01 mg / dL. It can be concluded that there is a low-purine diet counseling influences and high in omega-3s to decrease uric acid levels in gout patients with p = 0.004.